2020
DOI: 10.25225/jvb.20013
|View full text |Cite
|
Sign up to set email alerts
|

An update on the distribution and diversification of Rhabdomys sp. (Muridae, Rodentia)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 38 publications
5
24
0
Order By: Relevance
“…There are contact zones between the R. pumilio, R. bechuanae and R. intermedius that have been identified in the Free State at Sandveld (Ganem et al 2012;du Toit et al 2012;Ganem et al 2020); and at Fort Beaufort in the Eastern Cape (du Toit et al 2012;Ganem et al 2020). Other contact zones for R. d. chakae and R. d. dilectus are described from the northern Gauteng Province (Le Grange et al 2015, Ganem et al 2020. Altogether, fifteen contact zones for Rhabdomys have been documented in South Africa (Ganem et al 2020), and while one of these has been identified in the vicinity of the Eastern Cape Province in Fort Beaufort, this has been based on limited sampling despite the species being known to occur there.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…There are contact zones between the R. pumilio, R. bechuanae and R. intermedius that have been identified in the Free State at Sandveld (Ganem et al 2012;du Toit et al 2012;Ganem et al 2020); and at Fort Beaufort in the Eastern Cape (du Toit et al 2012;Ganem et al 2020). Other contact zones for R. d. chakae and R. d. dilectus are described from the northern Gauteng Province (Le Grange et al 2015, Ganem et al 2020. Altogether, fifteen contact zones for Rhabdomys have been documented in South Africa (Ganem et al 2020), and while one of these has been identified in the vicinity of the Eastern Cape Province in Fort Beaufort, this has been based on limited sampling despite the species being known to occur there.…”
Section: Introductionmentioning
confidence: 97%
“…Its distribution includes forest edges, where it is a pioneer species following forest clearances (Castley 1997). Rhabdomys is considered a species com-somal data (Rambau et al 2003;du Toit et al 2012;Ganem et al 2020). Of these, R. pumilio and R. dilectus were the first to be recognized based on chromosomal work combined with molecular data (Rambau et al 2003), with the latter further divided into two subspecies R. d. chakae and R. d. dilectus.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations